Use your head to get your foot in the door : job search secrets no one else will tell you - Mackay, Harvey (New York, N.Y. : Portfolio/Penguin, 2011)
Mackay shows readers how to prepare for the job search so they won't find themselves unemployed without a clue where to go next. Drawing on real-life stories of people who have transformed their lives by finding the right career, he shows how to: rebuild your personal confidence in the face of rejection, create a daily'recovery program' and job search, take advantage of the way firms and recruiters make hiring decisions, use state-of-the art networking strategies, and find job security even in today's tough economy. With his characteristic short, witty style, Mackay inspires readers to take charge of their careers, instead of letting the job hunt take charge of them.--From publisher description.
'This paperback edition with new chapters published 2011'--T.p. verso.
Includes index.
Keywords: Job hunting